2023
DOI: 10.1109/tuffc.2023.3263119
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating Data Mismatches in Deep Learning-Based Quantitative Ultrasound Using Setting Transfer Functions

Abstract: Deep learning (DL) can fail when there are data mismatches between training and testing data distributions. Due to its operator-dependent nature, acquisitionrelated data mismatches, caused by different scanner settings, can occur in ultrasound imaging. As a result, it is crucial to mitigate the effects of these mismatches to enable wider clinical adoption of DL-powered ultrasound imaging and tissue characterization. To address this challenge, we propose an inexpensive and generalizable method that involves col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Additionally, DL-based QUS approaches which are developed for specific machines, can be transferred to other machines at ease. Overall, in our prior work, we demonstrated that the transfer function approach has potential to provide an economical way to provide in-system transferability [9]. In this work, we demonstrate that transfer functions can be defined that can also provide out-system transferability, i.e., a Machine-to-Machine (M2M) transfer function.…”
Section: Highlightsmentioning
confidence: 76%
See 4 more Smart Citations
“…Additionally, DL-based QUS approaches which are developed for specific machines, can be transferred to other machines at ease. Overall, in our prior work, we demonstrated that the transfer function approach has potential to provide an economical way to provide in-system transferability [9]. In this work, we demonstrate that transfer functions can be defined that can also provide out-system transferability, i.e., a Machine-to-Machine (M2M) transfer function.…”
Section: Highlightsmentioning
confidence: 76%
“…Specifically, in several recent examples, CNNs were used to classify tissue states, and it was shown that they outperformed traditional QUS approaches [3]- [8]. Following this, in our previous work, a transfer function approach was developed using a calibration phantom to mitigate acquisition-related data mismatches within the same imaging machine for DL-based QUS approaches [9]. The transfer function approach significantly improved mean classification accuracies for pulse frequency, output power, and focal region mismatches within the same imaging machine, increasing them from 52%, 84%, and 85% to 96%, 96%, and 98%, respectively.…”
Section: Highlightsmentioning
confidence: 99%
See 3 more Smart Citations